Analisis Kekuatan Kolom Komposit Terbungkus Beton Berpenampang Bundar terhadap Kapasitas Tahanan Aksial dan Momen dengan Metode Beda Hingga - Rizki Aidil; Mukhlis Islam; Ade Sri Wahyuni; Agustin Gunawan; Yuzuar Afrizal (Inersia: Jurnal Teknik Sipil, 2024)
Composite column structures can provide high strength from the combination of two or more materials with different material properties which then provide better combined properties. This research was conducted by analysing the composite column structure with finite difference method and comparing the results with CSiCol application. The results of the analysis of   the Pn and Mn interaction diagram of the finite difference method composite column when compared to the CSiCol application composite column have a maximum percentage difference for the maximum Pn value of 19.17%, the maximum Mn value of 2.90%. The difference in the Pn and Mn values of  the composite column can be corrected with a regression equation using a linear correction factor and a Polinomial correction factor, with a maximum Pn percentage difference value of 8.93% for the linear correction factor and 6.84% for the Polinomial correction factor value. Therefore, the finite difference method can be used to analyse composite columns with relatively good accuracy provided that correction factors are used.